The Efforts to Increase Student Motivation Through Group Guidance Services in Class VII B: Upaya Meningkatkan Motivasi Belajar Siswa Melalui Layanan Bimbingan Kelompok di Kelas VII B - Ngesti Palupi (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2021)
This research was conducted based on phenomenon that exists in SMP N 4 Koto Baru which shows that there are students who have a low level of motivation to learn. Purpose of this study was to determine description of student learning motivation before receiving group guidance services, to determine description of student learning motivation after receiving group guidance services, and to find out whether learning motivation can be improved through group guidance services. Type of research used in this research is Action Research Guidance and Counseling by carrying out two cycles. Subjects of this study were 10 grade VII students of SMP N 4 Koto Baru consisting of 8 students with low learning motivation and 2 students who have high learning motivation, so that group dynamics occur. Data collection methods used were interviews, learning motivation scale and observation. Results showed that learning motivation of students before receiving treatment in form of group guidance was 44.4% in low category. After being given group guidance services at cycle I, student learning motivation increased to moderate category by 65%. Meanwhile, in cycle II student learning motivation continued to increase into high category with a gain of 74%. This shows that group guidance services can increase learning motivation in grade VII students at SMP N 4 Koto Baru.